Theory of Reasoned Action in IQSM to Increase Political Engagement in Millennial Generation - Musyarofah, Nurul (Research Horizon, 2024)
Political Involvement refers to any form of engagement or participation by citizens without formal authority in decision-making processes that can influence various aspects of citizens' lives. This implies that Political Involvement can be associated with a variety of factors and variables. This research aims to examine the influence of Reputation of social media (RSM), Information Quality of Social Media (IQSM), Social Media Political Marketing Activities (SMPMA), and Social Media Marketing Activities (SMMA) on Political Involvement. Additionally, the study explores the role of Trust as a mediating variable in the influence of RSM on Political Involvement. The research adopts a quantitative approach with a causal associative method and convenient sampling technique distributed online to 120 respondents through a digital survey using Google Forms. Independent variables include IQSM (X1), RSM (X2), SMPMA (X3), and Social Media Marketing Activities, while mediating variables consist of Trust (Z1), and the dependent variable is Political Involvement (Y). The analysis involves validity testing, reliability testing, model fit testing, and hypothesis testing. The research findings indicate that: Trust significantly mediates the positive influence of RSM on Political Involvement, IQSM does not have a positive and significant effect on Political Involvement, SMPMA does not have a positive and significant effect on Political Involvement, and SMMA has a positive and significant effect on Political Involvement. For future research, other variables that may influence Political Involvement beyond those used in this study could be considered.